Environmental and socio-economic impact dynamics in the development of urban areas - Ramzy Damasetio; Herdis Herdiansyah; Triarko Nurlambang (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: The development of the Bekasi Central Business District (BCBD) has not only changed the face of the city, but also reshaped the social, economic, and environmental relations of the surrounding community. The development of this area is positioned as an engine of economic growth, but in practice it can give rise to uneven impacts among social groups and pressure on the quality of the urban environment. This study aims to explore the environmental, social, and economic impacts of BCBD development based on the perceptions of people who live and work in the surrounding area. Methods: This study employed a qualitative approach using in-depth interviews with nine participants selected through purposive sampling from socio-economic groups living around the BCBD. The data were analyzed using thematic analysis to identify the patterns, dominant issues, and the relationship between the impacts felt by the community. Findings: This study examines how different socio-economic groups perceive and experience the impacts of BCBD development, thereby providing a comprehensive understanding of the social and environmental implications of urban business district growth. The results show that the development of the BCBD is perceived to bring economic benefits, such as increased employment opportunities and business activities, especially for groups. However, the community also expressed a reduction in access to open spaces, increased environmental pressure, and the emergence of spatial exclusivity that limits the involvement of the lower-middle economic groups. Conclusion: The conclusion of this study confirms the tension between the orientation of economic growth and the principles of socio-environmental sustainability in BCBD development. Novelty/Originality of this article: This study is among the first to examine the environmental, social, and economic impacts of a central business district in Bekasi, a growing satellite city of Jakarta. It extends the existing literature, which has largely focused on CBDs in primary metropolitan cities, by providing evidence from a secondary urban context.